(untitled) (Research, Society and Development, 2022)
The objective is to discuss about the actions produced or liable to the interventional production of Occupational Therapy with the homeless population, within the scope of the Street Office. This is an integrative literature review study, with qualitative analysis, which walks in order to answer the research question "What is there in the national and international literature on the work of the occupational therapist with the homeless population and within the scope of the Street Office?”, through the following steps: (1) elaboration of the guiding question; (2) search or sampling in the literature; (3) data collection; (4) critical analysis of included studies; (5) discussion of results; (6) presentation of the integrative review. Eleven studies were totaled in the final sample that responded to the objectives of the review and evidenced the occupational therapy practice based on the objectives of the service, in line with the specific attributions of the professional in the scenarios of Primary Health Care and the needs of the homeless population. It points to the use of artistic and cultural expression activities and the group approach as the main instruments of specific interventions used by the professional; use of light care technologies in the mediation of relationships; importance of knowing the context of life and performance of occupations in this scenario in order to promote the facilitation of involvement in significant occupations; work based on the perspective of harm reduction, on the promotion of well-being and quality of life and on the awareness and mediation of access to basic rights that guarantee the full exercise of citizenship.